Transport in Dilute Alloys - Kus, William Fred (My University, 1973)
The effect of a small concentration of nonmagnetic impurities or defects on the transport properties of a simple metal is investigated.
The correction to the Friedel Sum Rule, or displaced charge sum rule, due to the relaxation of the ions around an impurity, is calculated, and related to the volume change induced by the relaxation.
The finite temperature resistivity of dilute alloys of simple metals is studied in terms of the deviations from Matthiessen's Rule. An approximate theory, similar to the two band model, is presented. Detailed calculations based on this approximate theory as well as the complete expressions of a scattering time formalism for the resistivity, to include the effect of anisotropy in the electron-phonon interaction, are given for some alkali and aluminum alloys. The results are compared with experimental data and the prediction of other theories.
A simple theory for the finite temperature resistivity of a dilute alloy, which includes the effect of the strain field or relaxation of the ions around an impurity at finite temperature, is presented.
Keywords: Physics; Physics